Pengaruh Faktor Klimatik Terhadap Kepadatan Nyamuk Anopheles farauti di Ekosistem Pantai dan Rawa Provinsi Papua - Hanna S.I. Kawulur; Ivon Ayomi; Melda Suebu; Muhammad F. Rokhmad; Mardi R. Pardi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2019)
Infectious vectors are generally sensitive to environmental change, including climatic factor. Climate may affect the ability of vector in transmitting the disease. The purpose of this study was to determine the effect of climatic factors on density of Anopheles farauti Laveran in coastal and marsh ecosystems. The mosquito was collected by using human landing collection method. The climatic data recorded during the research were air suhue, wind velocity and humidity, while the rainfall rate data was obtained from the Provincial office of Meteorology and Geophysics Agency Suhue of Papua Province. The result showed that Anopheles farauti was constantly found during the study period as air suhue, humidity, rainfall and wind velocity fluctuated. This result suggest that during the data collection climatic factors did not significantly affect the presence and density of Anopheles farauti. Key words: climatic factor; mosquito density; coastal; swamp; Anopheles farauti.